Copernicus Sea Level Space Observations: A Basis for Assessing Mitigation and Developing Adaptation Strategies to Sea Level Rise - Legeais, Jean-François; Meyssignac, Benoît; Faugère, Yannice; Guerou, Adrien; Ablain, Michaël; Pujol, Marie-Isabelle; Dufau, Claire; Dibarboure, Gérald (Frontiers in Marine Science, 2021)
It is essential to monitor accurately current sea level changes to better understand and project future sea level rise (SLR). This is the basis to support the design of adaptation strategies to climate change. Altimeter sea level products are operationally produced and distributed by the E.U. Copernicus services dedicated to the marine environment (CMEMS) and climate change (C3S). The present article is a review paper that intends to explain why and to which extent the sea level monitoring indicators derived from these products are appropriate to develop adaptation strategies to SLR. We first present the main key scientific questions and challenges related to SLR monitoring. The different processing steps of the altimeter production system are presented including those ensuring the quality and the stability of the sea level record (starting in 1993). Due to the numerous altimeter algorithms required for the production, it is complex to ensure both the retrieval of high-resolution mesoscale signals and the stability of the large-scale wavelengths. This has led to the operational production of two different sea level datasets whose specificities are characterized. We present the corresponding indicators: the global mean sea level evolution and the regional map of sea level trends, with their respective uncertainties. We discuss how these products and associated indicators support adaptation to SLR, and we illustrate with an example of downstream application. The remaining gaps are analyzed and recommendations for the future are provided.